The possibilities of sludge management, generated in the industrial - laundry wastewater treatment process in the Fliegel Textilservice laundry in Nowe Czarnowo = Możliwości zagospodarowania osadów ściekowych powstających w procesie oczyszczania ścieków przemysłowych popralniczych na przykładzie pralni Fliegel Textilservice w Nowym Czarnowie - Bering, Sławomira; Mazur, Jacek; Tarnowski, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Sludge is generated in all methods of sewage treatment. Choosing a sewage treating technology is necessary to analyse simultaneously the possibilities of sludge management. The methods of sludge management, generated in the industrial sewage treatment processes, besides technological conditions, meet also law restrictions.
Keywords: zagospodarowanie osadów ściekowych; ścieki przemysłowe popralnicze; sludge management; industrial-laundry sewage